Let's join forces: boundary resources as enablers of value co-creation in e-commerce ecosystems - Tobias Wulfert; Gero Strobel; Hiep Hoang (Electronic Commerce Research, 2024)
Collaboration and value co-creation are important drivers of the continuous growth of e-commerce, which is expected to reach US 6.4 trillion in 2024 despite current global crises. Only a few transaction platforms currently dominate e-commerce (eg., Amazon, Walmart), but other participants are likely to join these platforms' ecosystems. Third-party developers can provide extensions to these ecosystems to enhance the platforms' functionality, but third-party developers' role in e-commerce ecosystems' success and generativity remains underexamined in academia. The present study scrutinizes the efficacy of boundary resources in attracting and managing third-party developers in e-commerce ecosystems. This investigation is predicated upon qualitative data gathered through interviews with 14 domain experts. The insights derived from these interviews have culminated in the formulation of seven design principles. These design principles are envisaged to serve as a guiding framework for owners of innovation and transaction platforms within the e-commerce sphere, facilitating the strategic deployment of boundary resources. It is anticipated that collaboration, value creation, and the overall generative capacity as well as the success of e-commerce ecosystems shall be considerably enhanced.
Keywords: 380; E-commerce ecosystem; Platform; Boundary resources; Design principles; Interview study